Cradle and all - Patterson, James (London : Headline Feature, 2000)
When a spate of supernatural events believed to be linked to the fulfilment of the Fatima prophecies occurs, Father Rossetti is chosen to interpret their meaning. But as the year 2000 approaches, he starts to believe that only a miracle can stop an unimaginable evil being unleashed on the world.
Keywords: Women private investigators -- Fiction; Thrillers (Fiction)